Response of Lemon Transplants to the Addition of Organic Fertilizer to Withstand Water Stress - Ashwaq Wadi Majeed; Altifat Fadhil Altaai (International Journal for Research in Applied Sciences and Biotechnology, 2022)
This experiment was carried out in lathhouse at University of Baghdad / college of Agricultural Engineering Sciences / Department of Horticulture and Landscape design during the two season 2019 and 2020 .The experience was conducted according to Split-split plots Within Design (RCBD) By three factors, the first factor was two -irrigation Intervals (every 3, 6 days), the second factor was three of rootstock (Volcamariana, Swingle Stromelo and sour orange) and the third factor organic fertilizer, was three concentrations, which is (0, 2.5 and 5 ml. L-1 / plant). Results showed that irrigation Intervals had a significant effect It has given ( every 3 days) increase in stem diameter, number of branches, number of leaves and Percentage of dry weight in branches. The citrus rootstock has exceeded with each other in the mentioned characteristics, while the organic fertilizer, has a significant effect in all the mentioned characteristics, as the concentration of 5 gm L-1 exceeds the treatment without adding fertilizer for the two seasons in respectively.